Transperineal MRI-US Fusion-Guided Target Biopsy of the Prostate after Abdominoperineal Resection: A Case Report - Nando De Vulder; Koen Geldof; Frederic Baekelandt; Katrien Gieraerts (Journal of the Belgian Society of Radiology, 2021)
Main Teaching Point: MRI-US fusion-guided transperineal prostate biopsy can help sampling clinically relevant prostate cancer in patients with a history of abdominoperineal resection and is feasible under local anaesthesia and in an outpatient setting. Prostate cancer remains one of the most diagnosed cancers in men worldwide. Prostate biopsy in patients with a history of abdominoperineal resection poses a serious challenge since transrectal ultrasound is not possible. Several techniques have been described with their respective limitations and risks. This report of such a patient aged 75, presents a Magnetic Resonance Imaging-Ultrasound fusion-guided transperineal approach to prostate biopsy which can be performed under local anaesthesia and in an outpatient setting.